Ознаки будови епідерми пластинки листка в таксономії видів та родів триби Bromeae (Poaceae) флори України - Красняк, О.І.; Федорончук, М.М. (Український ботанічний журнал, 2019)
З використанням сканувального електронного мікроскопа (СЕМ) досліджена епідерма пластинки листка 20 таксонів секцій Bromus, Bromopsis, Ceratochloa та Genea роду Bromus триби Bromeae, що трапляються в Україні, для оцінки таксономічного значення мікроморфологічних ознак та спроби вирішення деяких таксономічних проблем. Основні досліджені ознаки: розміщення та форма довгих, скрем'янілих та склепінчастих клітин, шипиків, трихом та клітин продихового апарата. Майже всі згадані типи клітин виявлені на абаксіальній та адаксіальній поверхнях листка. У секції Ceratochloa й у видів Bromus erectus, B. benekenii, B. ramosus не виявлено склепінчастих клітин, шипики не були знайдені в секції Genea й у деяких видів секції Bromopsis. За деякими мікроморфологічними ознаками склепінчастих, довгих клітин та шипиків види секції Bromopsis можна розділити на дві групи: до першої входять B. erectus, B. benekenii, B. ramosus, до другої – B. riparius, B. cappadocicus ( incl. Bromopsis heterophylla, B. calcarea, B. pseudocappadocica, B. cimmerica) і гібрид, відомий як "Bromopsis ×taurica" (nom. illeg.). Проміжне положення займає Bromus inermis. Інші мікроморфологічні ознаки є спільними для більшості таксонів. Тобто, досліджені ознаки епі- дерми пластинки листка переважно не є значущими для вирішення основних таксономічних проблем у трибі Bromeae. The leaf blade epidermis of 20 taxa of Bromus s. l. (sections Genea, Bromus, Bromopsis and Ceratochloa; tribe Bromeae) occurring in Ukraine were studied using SEM. The aim of the study was assessment of the taxonomic value of micromorphological characters and resolving some taxonomical and phylogenetical issues in the group. The main epidermal characters of leaf blades were shape, size and distribution of long cells, silica cells, crown cells, prickles, macrohairs, and cells of stomatal complexes, as well as cell wall shape, for some of them. Almost all mentioned types of cells occur on both abaxial and adaxial surfaces. The results show that crown cells were not observed in species of sect. Ceratochloa and in species B. erectus, B. benekenii, B. ramosus; prickles were not found in species of sect. Genea and some species of sect. Bromopsis. By some micromorphological characters (crown cells, prickles, and length of long cells), species of sect. Bromopsis can be subdivided into two groups. The first group consists of Bromus erectus, B. benekenii, and B. ramosus, the second one, of B. riparius, B. cappadocicus (incl. Bromopsis heterophylla, B. calcarea, B. pseudocappadocica, B. cimmerica), and the hybrid known as Bromopsis ×taurica (nom. illeg.). Bromus inermis have intermediate characters. Other micromorphological features (long cells, silica cells, macrohairs and cells of stomatal complexes) in the remaining taxa were common, their variability was high. It has been found that all studied characters of the leaf blade epidermis are not specifically useful for resolution of the main taxonomic issues within tribe Bromeae. According to the conducted analysis of micromorphological features, the genus Bromus s. l. in the flora of Ukraine comprises four section-rank taxa: sect. Bromus, sect. Genea (= genus Anisantha), sect. Bromopsis, and sect. Ceratochloa.